Nurturing Interpersonal Trust in Knowledge Sharing Intention towards Industry 4.0 - Chin, Tay Lee; Yean, Tan Fee (International Journal of Psychosocial Rehabilitation, 2020)
Knowledge management has captured the attention of researchers and practitioners. Knowledge sharing intention is the important element of knowledge management. Therefore, the purpose of this study is to examine the effect of interpersonal trust on knowledge sharing intention. Data was collected through self-administered questionnaires at higher institution education. The data was analyzed using Statistical Package for Social Science (SPSS) version 24. The findings show that interpersonal trust plays pivotal roles in promoting knowledge sharing intention. The implications of these findings are thoroughly discussed in the study.